PANDANGAN TOKOH AGAMA DAN TOKOH MASYARAKAT TENTANG ISTRI SEBAGAI PENCARI NAFKAH UTAMA DALAM KELUARGA - As’ad Hamdani; Istikharoh Istikharoh (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2022)
The purpose of this research is to describe the views of religious and community leaders on what arises from the wife's role as the main breadwinner for the family. This type of research is field research with a qualitative descriptive approach. The results of research on the impact that arises from the wife working as the main breadwinner in the family, there is disharmony in roles in the family and tensions of conflict in domestic life. The opinion of religious figures regarding wives who work is that before allowing their wives to work outside the home, husbands must consider the impact it will have on their family. And according to community leaders, the impact occurs because there are main driving factors, namely the lack of family economy and the husband's lack of income, so that many impacts arise, such as tension and conflict in the household which can lead to divorce.